Knee tuberculosis: a challenge in diagnosis and treatment - Ahmad, Muhammad Wafiuddin; Roslan, Ahmad Faizal; Zulkifly, Ahmad Hafiz (Faculty of Medicine & Health Sciences, Universiti Malaysia Sabah, 2021)
Tuberculosis (TB) is an ancient disease dated back from ancient Greece time. Once rare in developed countries, now it has re-emerged due to immigration and secondary immunodeficiency. A 27-year-old lady had left knee pain for the past 4 years, went for knee diagnostic arthroscopy procedure, and diagnosed as pigmented villonodular synovitis (PVNS) of the left knee. Despite regular analgesics and physiotherapy, patient symptoms worsen. Two years after the initial treatment, the patient went for a further workout and diagnosed as knee tuberculosis, commenced on anti-TB treatment, the patient still left complicated with a stiff knee and fixed flexion deformity. Identification of knee tuberculosis during the initial phase is crucial as late diagnosis and treatment will leave the patient with debilitating complications.